Health system impacts of SARS-CoV − 2 variants of concern: a rapid review - Justine Dol; Leah Boulos; Mari Somerville; Lynora Saxinger; Alexander Doroshenko; Stephanie Hastings; Bearach Reynolds; Allyson Gallant; Hwayeon Danielle Shin; Helen Wong; Daniel Crowther; Marilyn Macdonald; et al. (BMC, 2022)
Abstract Background As of November 25th 2021, four SARS-CoV − 2 variants of concern (VOC: Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), and Delta (B.1.617.2)) have been detected. Variable degrees of increased transmissibility of the VOC have been documented, with potential implications for hospital and health system capacity and control measures. This rapid review aimed to provide a synthesis of evidence related to health system responses to the emergence of VOC worldwide. Methods Seven databases were searched up to September 27, 2021, for terms related to VOC. Titles, abstracts, and full-text documents were screened independently by two reviewers. Data were extracted independently by two reviewers using a standardized form. Studies were included if they reported on at least one of the VOC and health system outcomes. Results Of the 4877 articles retrieved, 59 studies were included, which used a wide range of designs and methods. Most of the studies reported on Alpha, and all except two reported on impacts for capacity planning related to hospitalization, intensive care admissions, and mortality. Most studies (73.4%) observed an increase in hospitalization, but findings on increased admission to intensive care units were mixed (50%). Most studies (63.4%) that reported mortality data found an increased risk of death due to VOC, although health system capacity may influence this. No studies reported on screening staff and visitors or cohorting patients based on VOC. Conclusion While the findings should be interpreted with caution as most of the sources identified were preprints, evidence is trending towards an increased risk of hospitalization and, potentially, mortality due to VOC compared to wild-type SARS-CoV − 2. There is little evidence on the need for, and the effect of, changes to health system arrangements in response to VOC transmission.